Mikhail Gorbachev –at the Origins of a Soviet Reformist’s Politi-cal Career - Bulignia, Tamara Alexandrovna (Acta Scientiarum Socialium, 2016)
Mikhail Gorbachev – at the origins of a Soviet Reformist’s political career.This article presents the family background and early years of life of Mikhail Gorbachev, later to become the first man of the Soviet Union. His person is associated with glasnost, perestroyka, the end of the Cold War and the collapse of the Soviet Union. After graduating from Moscow State University, Gorbachev returned to his homeland, the Stavropol Region. The article draws attention to some interesting moments in Gorbachev’s early career, which later played an important role in his rise to power. He was regarded an agricultural expert in the Stavropol Regional Party Committee, the Stavropol Region being considered one of the most important agricultural areas in the USSR. The region was also very famous for its mineral water springs and sanatoriums; therefore, it was a favourite holiday resort of the highest party and state leaders. Gorbachev, who in 1970 was appointed First Party Secretary of the Stavropol Regional Committee, was responsible for organizing their stay in the Stavropol Region. It gave him a possibility to build up good relations with Brezhnev, Gromiko and Andropov among others. His career was also promoted by CC and PB member Fyodor Kulakov, his predecessor at the head of the Stavropol regional party organisation. The Stavropol period in Gorbachev’s life ended in 1978, when he was elected a CPSU CC secretary.
Keywords: Stavropol; Gorbachev; Communist Party of the Soviet Union; party career